Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1149/1.1543566
|View full text |Cite
|
Sign up to set email alerts
|

Conduction in Multiphase Particulate/Fibrous Networks

Abstract: Several promising Li-ion battery technologies incorporate nanoarchitectured carbon networks, typically in the form of whisker/ particle blends bonded with thermoplastic binders to form the anodes. Degradation of these materials is currently a persistent problem, with damage presenting as blistering and/or delamination of the electrode. Both material composition and morphology play a role in these critical failure modes, and are explored in the present work as they affect conduction in practical battery materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 36 publications
1
48
0
Order By: Relevance
“…Mesoscale modeling has allowed the simulation of transport and mechanics in complex architectures of packed agglomerates, 26 but a full predictive theory of chemical energy storage systems still requires fundamental research and methodological developments in several key areas. Progress in these key areas will eventually allow higher energy and power at lower cost and will dramatically accelerate innovation in new materials.…”
Section: The Role Of Theory and Modeling In Electrical Energy Storagementioning
confidence: 99%
“…Mesoscale modeling has allowed the simulation of transport and mechanics in complex architectures of packed agglomerates, 26 but a full predictive theory of chemical energy storage systems still requires fundamental research and methodological developments in several key areas. Progress in these key areas will eventually allow higher energy and power at lower cost and will dramatically accelerate innovation in new materials.…”
Section: The Role Of Theory and Modeling In Electrical Energy Storagementioning
confidence: 99%
“…Also parameters of the electrode manufacturing process are affected by the nature of the conductive additive. Particle size and shape are important properties of the electrochemically active electrode material when combining it with the ideal conductive additive [15][16][17][18][19]. In addition, Wang et al showed that part of the conductive carbon black is incorporated in the polymer binder used in the electrode and that the resulting highly conductive polymer electronically connects the electrode particles [20].…”
Section: Introductionmentioning
confidence: 99%
“…As the specific energy and energy density of the cell is optimized by keeping the respective amount and volume fraction of conductive carbon as low as possible, there is bound to be a trade-off between cell energy and power. With increasing amount of conductive carbon the electrical electrode resistivity decreases by following more or less distinct percolation curves whose shapes depend on both the type of electrochemically active material and the conductive carbon [14,19]. When increasing the volume fraction of the conductive carbon in the electrode, the electrical electrode resistivity remains at a high constant level until the critical volume fraction is reached where the electrical resistivity of the electrode sharply drops to a lower resistivity level.…”
Section: Introductionmentioning
confidence: 99%
“…Mandal et al [14] showed that both the electronic conductivity and the discharge capacity of LiMn 2 O 4 cathodes depended on conductive-additive content. Sastry and coworkers [15,16] have shown theoretically that the shape of the conductive material has a substantial effect on the conductivity of the network formed. In particular, an increase in the aspect ratio of the filler improves the conductivity of the network for a given volume fraction of additive.…”
Section: Introductionmentioning
confidence: 99%